Pendekatan STEM Melalui Model PjBL Pada Materi Sel Volta Untuk Mengembangkan Kemampuan Psikomotor Siswa - Amarlita, Dhamas Mega; Ningsih, Endang Utami (LP2M IAIN Ambon, 2025)
STEM Approach through PjBL Model on Voltaic Cell Material to Develop Students' Psychomotor Skills. Learning not only focuses on aspects of knowledge and attitudes but also skills or psychomotor abilities. Especially in chemistry learning, psychomotor skills are an important aspect because they involve a lot of activities in the ability to use tools, materials and technology. One of the relevant approaches is the STEM (Science, Technology, Engineering and Mathematic) approach applied through the PjBL (Project Based Learning) learning model. This study aims to describe the psychomotor skills after the application of the STEM approach through the PjBL model on “Sel Volta” material. Based on the results of the study, it is known that the learning can build students' psychomotor abilities well with the results obtained in the excellent category of 73.17%, good by 21.95%, and sufficient by 4.88%.